Analisis Kelayakan Finansial Penangkapan Ikan di Waduk Koto Panjang Kabupaten Kampar Provinsi Riau - Warningsih, Trisla; Djokosetiyanto, D; Fahrudin, Achmad; Adrianto, Luky (Fakultas Perikanan dan Kelautan Universitas Riau, 2016)
This study aimed to analyze the financial feasibility of fish catching in Koto Panjang Reservoir of Kampar District, Riau Province, using business and investment criteria analyses. The result showed that each engine boat and rowboat has IDR 29,313,301.59 and IDR 15,044,311.11 for their respective profit; 3.55 and 3.48 for their respective Revenue-Cost Ratio Value; 0,29/yr or 3.3 months and 0.30/yr or 3.6 months for their respective fishermen payback period; and 3.6 % and 4 % for their respective Return on Investment (ROI) value. Investment criteria analysis on fish catching for each engine boat and rowboat obtained Net Present Value (NPV)of 142,169,973.13 and 72,313,686.96, respectively; 3.01 and 2.91 for their respective Net B/C value; 49% and 46% for their respective Internal Rate of Return (IRR) value. Fish catching business in Koto Panjang Reservoir is deemed feasible because NPV>0, IRR>interest rate, and B/C>1 for both engine boat and rowboat